Assessment of the Impact of CBN Post COVID-19 Stimulus Packages on the Economic Sustainability of SMEs in the COVID-19 Epic Centres of Nigeria - Okoh, Johnson Ifeanyi; Mac-Ozigbo, Ada; Onyemauche, Oparaduru John; Aderemi, Timothy Ayomitunde (The Journal of Accounting and Management, 2022)
In this study, efforts have been made to investigate the economic impact of CBN Post COVID-19 stimulus packages on the sustainability of SMEs in Nigeria with focus on three epic centres, Lagos state, Ogun state and FCT. Consequently, 600 SMEs were selected for the survey, in which sufficient information was eventually gathered and utilized from 568 respondents. The economic sustainability of SMEs was measured by SMEs profitability and SMEs stock of goods, in which the impact of CBN Post COVID-19 stimulus packages on these variables were assessed using statistical and econometric techniques respectively. It is instructive to state that the findings in this study are summarized as follows; CBN Post COVID-19 stimulus packages and economic sustainability of SMEs in the three epic centres, Lagos state, Ogun state and FCT have a positive and significant relationship. This implies that economic sustainability of SMEs was significantly enhanced by CBN Post COVID-19 stimulus packages in the selected COVID-19 epic centres in Nigeria. In the light of the above, this study makes the following recommendations for the policymakers in Nigeria.The CBN post COVID-19 stimulus packages targeted at SMEs in COVID-19 epic centres should be sustained, and extended to all parts the federation. Also, due to the significant volume of profitability recorded by the selected SMEs, the current interest rate and the moratorium on the on CBN intervention should be sustained by the policymakers.